The Implementation of the TGT (Team Game Tournament) Cooperative Learning Model Using Monopoly Games to Increase the English Reading Skills of Eighth-Grade Students at MT's Roudlotur Rosmani, Bengkulu City - Bambang Rusdiyanto; Ali Akbarjono; Feny Martina (The Future of Education Journal, 2026)
Reading Comprehension of eighth grade students at MTs Roudlotur Rosmani Kota Bengkulu often presents challenges such as difficulty understanding main ideas, text meaning, text types, and unfamiliarity with new vocabulary. This study used The Team Game Tournament (TGT) model of cooperative learning because considered capable of addressing these issues. To evaluate the improvements achieved, this study employed a pre-test and post-test experimental design involving 18 participants. Significant differences were found in the final exam scores in the experimental class that implemented TGT model achieved higher scores than the control class, which used only conventional teaching methods without TGT. The TGT-based experimental class achieved an average score of 83.11, while the control class, which used a conventional learning model, achieved an average score of 54.67. The N-Gain analysis showed an N-Gain score of 73.01% for the experimental class, indicating that the use of TGT had a significant effect.